Citrus orchard biodiversification pathways: evidence for climate and water resilient orchards in North Africa - Mahjoub, Imene; Chebbi, Rim Zitouna; Temani, Fida; Ben, Youssef Salah; Mekki, Insaf; Zairi, Abdelaziz; Jacob, Frederic (International Center for Agricultural Research in the Dry Areas, 2024)
This report describes a joint research between Tunisia as satellite site and Morocco (Tensift basin), on climate smart orchard systems, given the similarities in physical and social aspects, the complementarities in scientific approaches and longstanding climate and food security research collaboration with local partners (e.g. UM6P and the consortium on water management, climate and remote sensing-based innovation). The overall aim was to test water conservation and diversification innovations through the intercropping of multiservice crops (vetche, triticale, oat) in citrus orchard systems and to co-create climate and water smart decision-support tools for farmers, practitioners and policymakers to improve the climate resilience of this important agricultural sector.